EVALUATION OF ANTIMICROBIAL AND ANTIOXIDANT ACTIVITY OF STEM AND LEAF EXTRACTS OF COSCINIUM FENESTRATUM - W.Goveas, Santhosh; Abraham, Asha (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective:In the present study, antioxidant activity and antibacterial activity leaf and stem extracts of Coscinium fenestratum wasÂ investigated. Methods:To asses the antioxidant activity, methanolic leaf and stem extracts were used. Free radical scavenging activity was evaluated using 1,1-diphenyl-2-picryl-hydrazyl (DPPH) and 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) or ABTS. For antimicrobial activity, aqueous, acetone, ethanol and methanloic extracts of stem and leaf extracts were tested for its potent antimicrobial activity against Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa and Bacillus subtilis.Total content of phenol and flavonoid was quantitatively estimated in leaf and stem extracts of Coscinium fenestratum. Results &Conclusion: Total phenoilc content in the stem and leaf was found to be 8.35Â±0.56 and 3.35Â±0.67 mg GAE/g extract, While Â the total flavonoid content in the stem and leaf were found to beÂ 12.8Â±0.88 and 3.2Â±0.78 mg QE/g extract respectively. Among the different extracts, methanolic stem extract showed moderate activity against E.Coli (17Â±0.33),P.aeruginosa (12Â±0.20), B.subtilis (13Â±0.45).Methanol leaf extract had maximum activity against S.aureus(6.4Â±0.67) and lowest against B.subtilis (3.9Â±0.58) respectively. Key words: Coscinium fenestratum, Antioxidant , Antimicrobial,Â DPPH, Medicinal plant, Phenol, Free radical.